Composting as a tool for environmental management of quails’ carcasses - Valente, Beatriz Simões; Xavier, Eduardo Gonçalves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
A trial was conducted to evaluate composting as a tool for environmental management of quails’ carcasses. A completely randomized design was used with two treatments and four replications. The proportions of residues were: 1kg of carcasses of quails: 1kg of wood shavings (T1) and 1kg of carcasses of quails: 1kg of wood shavings: 1kg of avian bed (T2). The temperature of composting mass was evaluated during 35 days of composting. The following analyses were performed: pH, moisture, total organic matter, ash, total organic carbon, total nitrogen and C/N ratio. According to the results herein obtained, 0.30m height wood boxes are not adequate for composting of carcasses of quails. The utilization of avian bed from one lot of broilers as inoculum speeds up the decomposition of a mixture of wood shavings and quails’ carcasses.